Anticipative strategic production technology planning considering cyclic interactions. (November 2018) - Schönmann, A.; Dengler, C.; Reinhart, G.; Lohmann, B.
Abstract: Application of the most efficient and effective production technologies is seen as a key driver for production companies in high wage countries to be successful in a turbulent market environment. However, in order to anticipate the future suitability of a production technology, a company's internal and external influencing factors need to be considered and uncertainties need to be modeled in an adequate manner. Some factors within the production environment manifest themselves as temporally and structurally recurring patterns (defined as cycles) and their future progress is predictable to a certain extent. In this paper, the cyclic behavior of relevant influencing factors for determining a technology's suitability from a strategic point of view is modeled using a continuous time recurrent fuzzy system (CT-RFS). In addition to the visualization of the future development of the evaluation criteria maturity, potential and costs, the resulting suitability is calculated taking uncertainties into account.